Effects of algebraic reasoning integration of computational thinking on word problem-solving in an international school in Malaysia - Ku, Soh Ting (2022)
Word problems solving refers to the students’ ability on interpreting the problems, converting their knowledge into mathematical statements, and then doing arithmetic computations. In this study, the strength and precision of students' word problem-solving skills based on their additive and logical reasoning are studied. This study expanded coding by integrating it with the computational thinking and algebra reasoning that strengthened the communication, collaboration, logical reasoning, additive reasoning, and word problem solving abilities among students. The algebraic reasoning integration of computational thinking (AR-CT) instructional design was developed from the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). Sequential mixed method approaches incorporating interview, systematic literature review, and quasiexperimental procedures were used to collect the data. The experimental group (AR-CT) and the conventional instruction as control group (CVI) were investigated in this research. Through paired t-test results, the AR-CT group intervention outperformed than CVI group in terms of word problem solving, additive reasoning, and logical reasoning. Meanwhile, the impacts of the prior knowledge of arithmetic, computational thinking and ability of word problem solving on the effectiveness of AR-CT on performance of word problem solving are studied. When the analysis of covariance (ANCOVA) was adjusted for prior knowledge, the post-test of word problem-solving skills and additive reasoning remained significant, but not for logical reasoning. The results shown the students is increasingly affected in the order of prior computational thinking followed by prior arithmetic knowledge and word-problem solving skills, which these factors are selected as statistical covariates in this analysis. Adoption of AR-CT instructional strategy in math lessons can improve the additive reasoning however, there is no sign of enhancement on the logical reasoning of the students. The modules' benefits students’ pre-algebra concepts and coding when solving word problems. Meanwhile, encouraging teachers to interact with students and teachers' creativity in creating excellent teaching situations.